1992
DOI: 10.4319/lo.1992.37.6.1221
|View full text |Cite
|
Sign up to set email alerts
|

Growth and production of planktonic protozoa in Lake Michigan: In situ versus in vitro comparisons and importance to food web dynamics

Abstract: Growth of an entire planktonic protozoan community in Lake Michigan (nanoflagellates, microflagellatcs, and ciliates) was measured on 10 dates in 1988-l 989 in fractionated lake water (<3, ~8, < 30, and < 153 pm) incubated in bottles (in vitro), while in June and July 1989, in vitro growth rate estimates were compared with in situ growth rates derived from the mitotic index. Comparisons of in situ vs. in vitro growth rates for the taxa assayed were similar, indicating that in vitro experiments provide reasonab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 42 publications
2
38
1
Order By: Relevance
“…Vertical watercolumn sampling (June-November 1991, n = 9) indicated that both phytoplankton chlorophyll and carbon were relatively constant with depth but increased dramatically on the bottom of the lake. This was due to a meroplanktonic algal maximum existing in a flocculent lake bottom layer -0.05 m thick (see Carrick et al 1993a). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Vertical watercolumn sampling (June-November 1991, n = 9) indicated that both phytoplankton chlorophyll and carbon were relatively constant with depth but increased dramatically on the bottom of the lake. This was due to a meroplanktonic algal maximum existing in a flocculent lake bottom layer -0.05 m thick (see Carrick et al 1993a). …”
Section: Resultsmentioning
confidence: 99%
“…Ranges for total P are -100-500 p,g liter-l while total N values range from 3,000 to > 11,000 pg liter-l (Schelske et al 1992). Concentrations of NO,--N + NO,--N and P043--P are low (<2 pg liter-'), and ammonium (NH,+-N) concentrations are generally <5 pg liter-l (St. John's River Water Management District unpubl.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations